2015
DOI: 10.1016/j.nicl.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Mapping abnormal subcortical brain morphometry in an elderly HIV + cohort

Abstract: Over 50% of HIV + individuals exhibit neurocognitive impairment and subcortical atrophy, but the profile of brain abnormalities associated with HIV is still poorly understood. Using surface-based shape analyses, we mapped the 3D profile of subcortical morphometry in 63 elderly HIV + participants and 31 uninfected controls. The thalamus, caudate, putamen, pallidum, hippocampus, amygdala, brainstem, accumbens, callosum and ventricles were segmented from high-resolution MRIs. To investigate shape-based morphometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 42 publications
3
33
1
Order By: Relevance
“…Previous research has associated nadir CD4 count 14,15 and duration of known HIV infection 13,17 with measures of brain structure, although not universally. 10,16,19 The nature of the participants in these studies differs substantively from ours. In general, HIV-positive individuals in our study were older, and all were effectively treated with cART and had higher CD4 counts.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Previous research has associated nadir CD4 count 14,15 and duration of known HIV infection 13,17 with measures of brain structure, although not universally. 10,16,19 The nature of the participants in these studies differs substantively from ours. In general, HIV-positive individuals in our study were older, and all were effectively treated with cART and had higher CD4 counts.…”
Section: Discussioncontrasting
confidence: 69%
“…Our findings favor the latter interpretation, as we found no relationship between brain-PAD score and chronological age or duration of HIV diagnosis. This fits with evidence from neuroimaging studies that have demonstrated independent effects of aging and HIV on the brain, 10,11,16,19,29 and does not support reports of accelerating effects. 12,21,30 However, these previous studies often included a preponderance of untreated individuals, those with detectable HIV viremia, or younger adults (i.e., <50 years old).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Most notably, VBM analysis revealed reductions in WM tissue density in the brainstem and thalamus. These results are consistent with several prior studies that have reported volume loss in similar regions 7,11,13,29,30 , including diffusion tensor imaging studies that show loss of WM integrity in the thalamus and brainstem of HIV-infected patients 31,32 . The findings here support the hypothesis that subcortical structures are particularly vulnerable to the virus 33 , and add spatial detail regarding the distribution of atrophy.…”
Section: Discussionsupporting
confidence: 92%
“…The neuroanatomic structures involved in HIV infection are largely consistent across the various imaging modalities, with the most common affected brain regions being the frontal white matter (FWM) [38, 39], basal ganglia (BG) [42, 43, 38, 39], and the thalami [42]. The effect of HIV infection on frontostriatal circuitry was similarly reported by a meta-analysis combining six task-based functional MRI (fMRI) studies (n=105 HIV-infected and n=102 HIV-uninfected controls) where frontostriatal dysfunction correlated to degree of cognitive impairment, disease progression, and treatment effect [44].…”
Section: Cns Imaging In Hivmentioning
confidence: 99%